Three new Raspailiidae Hentschel, 1923 (Axinellida, Demospongiae) from Peru - Recinos, Radharanne; Pinheiro, Ulisses; Willenz, Philippe; Hajdu, Eduardo (Zootaxa, 2020)
Currently 26 sponge species are known for the Peruvian coast, but so far no raspailiids had been recorded from this region. Raspailiidae are distributed worldwide and its species are characterized by encrusting, massive, lobate, fan-shaped or branching growth forms, usually with a very hispid surface. In the present study, three new species of Raspailiidae are described from the Peruvian coast. Two new Eurypon spp. were collected at Islas Lobos de Afuera (Lambayeque). Eurypon lacertus sp. nov. is a thinly encrusting orange sponge with choanosomal skeleton composed of large tylostyles and small acanthostyles, and ectosomal skeleton with anisoxeas. Eurypon hookeri sp. nov. is a crustose, ruby red sponge, with choanosomal skeleton composed of large (subtylo)styles and acanthostyles, and ectosomal skeleton pierced by acanthostyles and (subtylo)styles, often surrounded by bouquets of smaller styles. The third new species, Plocamione matarani sp. nov., was collected at Matarani (Arequipa). It is a thinly encrusting orange sponge, the only Plocamione with two categories of choanosomal styles, and a single category of ectosomal styles, acanthostyles and anisoacanthostrongyles. These are the first records of Eurypon and Plocamione for the Peruvian coast, and the entire Southeastern Pacific, in the case of the latter.